INFORMATION SHARING AND MECHANISM IN ONLINE COMMUNITY: A NETNOGRAPHY STUDY - Septiane Andriane; Ave Adriana Pinem; Putu Wuri Handayani (Jurnal Sistem Informasi, 2019)
The emergece of C2C (customer to customer) community in e-commerce platform is expected to boost the number of SME moving to online plaform. Since the community could provide information and experience required by new e-commerce players. This study aims to analyse what information is shared by members in C2C community and what is the information sharing mechanism that implemented on it. Netnographic study was conducted by observing 1002 posts from the Bukalapak community for six months. As Bukalapak is one of the largest C2C platfom in Indonesia. The result shows that the information shared could be classified by keyword in to five classes, namely categories of tips and tricks, ideas and problems with third parties, ideas and problems of features, community, and question and answer. The information category that has not been covered by Bukalapak original categories is and problems with third parties which mentioned in many posts by community member. The mechanisms used to share the information are including, standard, policy, status and reward.